Sustainability scenarios for the New Space tourism industry - Toivonen, Annette (Matkailututkimus, 2022)
The following piece is based on the lectio praecursoria presented at the defence of the doctoral dissertation ‘The emergence of New Space: a grounded theory study of enhancing sustainability in space tourism from the view of Finland’, which was publicly defended on 22 April 2022, at Rovaniemi, University of Lapland. The full version of the dissertation can be found at https://urn.fi/URN:ISBN:978-952-337-311-2.